The effects of trace element supplementation on glycolipid metabolism in PCOS: a systematic review and meta-analysis - Yang, Liuzhen; Gao, Yi; Zhao, Wei; Qi, Yuwen; Duo, Xinru; Wang, Huixia (Frontiers in Nutrition, 2025)
ObjectivesA common endocrine and metabolic condition affecting women of reproductive age is polycystic ovarian syndrome (PCOS). The link between trace elements and PCOS has drawn more attention in recent years. However, the complete therapeutic potential of trace element supplementation in PCOS therapy is still unknown. Thus, the purpose of this study is to look at how supplementing with four trace elements– calcium, chromium, selenium and magnesium–may affect the metabolism of glycolipids and other clinical outcomes in women with PCOS.MethodsTo find randomized controlled trials (RCTs), a comprehensive literature search was carried out up until May 2025 using four internet databases: the Cochrane Library, Web of Science, Embase, and PubMed. Intervention studies that evaluated the impact of calcium, chromium, selenium and magnesium supplementation on important outcomes such as blood glucose levels, lipid profiles, oxidative stress markers, inflammatory responses, sex hormone concentrations, and body weight in PCOS patients met the inclusion criteria. Heterogeneity between studies was evaluated using the I2 statistic, a result of more than 50% indicates significant heterogeneity.ResultsA total of 25 RCTs with a combined sample size of 1,600 PCOS patients were considered. The results showed a significant decrease in fasting blood glucose levels (SMD = −0.79, 95% CI: −1.11 to −0.46). Both insulin resistance as determined by homeostasis model assessment of β-cell function (SMD = −0.68, 95% CI: −1.00 to −0.36) and fasting insulin levels were significantly lower (SMD = −0.58, 95% CI: −0.90 to −0.26). Additionally, it was discovered that taking supplements of selenium increased the QUICKI index (SMD = 0.53, 95% CI: 0.15 to 0.91) and considerably decreased fasting insulin concentrations (SMD = −0.32, 95% CI: −0.63 to −0.01). Magnesium supplementation did not show statistically significant impacts on any glucose metabolic measures, however neither fasting plasma glucose nor HOMA-IR showed any statistically significant effects. Chromium supplementation was observed to significantly lower levels of very-low-density lipoprotein (SMD = −0.59, 95% CI: −0.91 to −0.27) and triglycerides (SMD = −0.59, 95% CI: −0.91 to −0.27) in relation to lipid metabolism. Other lipid measures, such as total cholesterol, low-density lipoprotein cholesterol, and high-density lipoprotein cholesterol, did not, however, show any statistically significant changes. Supplementing with magnesium or selenium had no statistically significant effects on any of the lipid metabolic markers. Calcium supplementation was observed to significantly lower levels of nitric oxide (SMD = −0.45, 95% CI: −0.84 to −0.06) and malondialdehyde (SMD = −0.76, 95% CI: −1.15 to −0.36) in relation to oxidative stress markers. Malondial-dehyde levels (SMD = −1.69, 95% CI: −3.10 to −0.28) and high-sensitivity C-reactive protein levels (SMD = −0.65, 95% CI: −1.05 to −0.24) were shown to be considerably reduced by chromium supplementation. Furthermore, a noteworthy rise in total antioxidant capacity was linked to it (SMD = 1.47, 95% CI: 1.02 to 1.92). Malondial-dehyde and inflammatory cytokines did not show any statistically significant changes, while selenium supplementation was shown to significantly increase total antioxidant capacity (SMD = 0.55, 95% CI: 0.16 to 0.95). None of the oxidative stress markers were significantly regulated by magnesium; The levels of sex hormones, including follicle-stimulating hormone, luteinizing hormone, dehydroepiandrosterone, sex hormone-binding globulin, testosterone, total testosterone, and the free androgen index, did not significantly improve with supplementation of chromium, calcium, magnesium, and selenium; Across all trace element supplementation regimens, no statistically significant variations were seen in weight-related measures, including body weight, waist circumference, hip circumference, and body mass index. Further high-quality randomized controlled studies are necessary to validate the low efficacy of calcium and magnesium, across the majority of outcome measures.ConclusionIn PCOS patients, chromium has a clear therapeutic benefit in reducing oxidative stress, dyslipidemia, and glucose metabolic disorders. Selenium has demonstrated promise in raising antioxidant capacity and boosting insulin sensitivity.